Effects of monoterpenes on glucose uptake and lipid metabolism in 3T3-L1 adipocytes / Tan Xien Cherh - Tan, Xien Cherh (2016)
Various strategies have been adopted to combat complications caused by Type 2 diabetes mellitus (T2DM) and diet control is one of them. Monoterpenes, the major constituents of essential oils, are synthesized and widely used as artificial food flavours. The aims of the present study were to assess the effects of twelve monoterpenes on antioxidant capacity, glucose uptake and lipid metabolism. Antioxidant capacity of monoterpenes were assessed using to 2, 2-diphenyl-2-picrylhydrazyl (DPPH) and 2, 2ï¿½- azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assays. In vitro alpha-amylase and alpha-glucosidase inhibitory assays were used to assess the potential anti-hyperglycaemic property of monoterpenes. The 3T3-L1 cellular model was used to assess the effects of monoterpenes on adipocyte differentiation, lipid accumulation, glucose uptake and lipolysis. Gene expression study was conducted to determine the potential mechanisms involved in the above mentioned processes. Results showed that the monoterpenes used in the current study exerted low DPPH and ABTS radical scavenging activity even at high concentrations. Some monoterpenes inhibited alpha-glucosidase activities and stimulated glucose uptake and lipolysis in 3T3-L1 adipocytes. (R)-(+)-Limonene stimulated both glucose uptake (17.4%) and lipolysis (17.7%); in parallel, the mRNA expressions of glucose transporter 1 (GLUT1) was upregulated, glucose transporter 4 (GLUT4) was unaffected, and mRNA expression of adipose triglyceride lipase (ATGL) was suppressed. Oil Red O quantitative results showed that low level oxidative stress induced by glucose oxidase was able to stimulate both adipogenesis and lipid accumulation in 3T3-L1 adipocytes though mRNA expression of glutathione peroxidase (GPx) remained unaffected. The effect of glucose oxidase in adipogenesis and lipogenesis was not affected by the addition of monoterpenes. Taken together, the selected monoterpenes may not confer strong iv protection against free radicals but nevertheless, their positive influence on lipid and glucose metabolism may have potential in the control of obesity and T2DM